2014
DOI: 10.1093/rof/rfu003
|View full text |Cite
|
Sign up to set email alerts
|

Small Banks and Local Economic Development*

Abstract: This paper discusses the effects of small banks on economic growth. We first theoretically show that small banks operating at a regional level can spur local economic growth. As compared with big interregional banks, small regional banks are more effective in promoting local economic growth, especially in regions with lower initial endowments and severe credit rationing. We then test the model predictions using a sample of German banks and corresponding regional statistics. We find that small regional banks ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
44
0
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 134 publications
(54 citation statements)
references
References 66 publications
7
44
0
3
Order By: Relevance
“…Although we do not find evidence that foreign banks reduced lending, our results indicate that cooperative banks are important for the development of SME enterprises. Moreover, our results are in line with the findings of Hakenes et al (2014), who documented that small regional banks can give local entrepreneurs a competitive edge and promote local economic growth, especially in underdeveloped regions, such as the CEE post-transition countries.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Although we do not find evidence that foreign banks reduced lending, our results indicate that cooperative banks are important for the development of SME enterprises. Moreover, our results are in line with the findings of Hakenes et al (2014), who documented that small regional banks can give local entrepreneurs a competitive edge and promote local economic growth, especially in underdeveloped regions, such as the CEE post-transition countries.…”
Section: Discussionsupporting
confidence: 92%
“…As a result, our findings suggest that cooperative banks are important for the development and performance of small businesses in post-transition countries. Hence, our results are in line with Hakenes et al (2014), who documented that small regional banks are more effective in promoting local economic growth, especially in underdeveloped regions.…”
Section: Introductionsupporting
confidence: 92%
“…A facilitating role of local financial development and banks with regional orientation for regional economic activity has been highlighted, for example, by Carbó Valverde and Rodríguez Fernández ( ), Guiso et al . ( ), or Fernández de Guevara and Maudos ( ), or more recently, Hakenes et al ( ). Bank outreach (and its dynamics) also impacts monetary policy, which is less effective if the market is dominated by a few large banks (Ghossoub and Reed, ), and, as a potential further argument for preserving rural bank structures, Shaffer ( ) actually observes cost diseconomies of urbanization (for U.S. banks).…”
Section: Review Of Connected Literaturementioning
confidence: 97%
“…The study of Sui (2011) pointed to information disclosure, Burger and Warnock (2005) identified growth rates, the research of Ayala et al (2017) detected global cyclical factors, while Rajan and Zingales (2003) and Eichengreen and Leungnareumitchai (2004) openness of the economy and internationally recognized accounting standards respectively. The factor of size the country and lending to SME segment, foreign ownership of the banks were identified by the majority of the studies as influencing the development of the corporate bond market: Mu et al (2013), Bae (2012) Eichengreen et al (2008), Braun and Briones (2006), Burger and Warnock (2005), Eichengreen and Leungnareumitchai (2004); and Astrauskaite (2016), Behr et al (2015), Hasan et al (2014), Hakenes et al (2014), Popov and Udell (2012), Bae (2012), Stewart (2009), Adelegan and Radzewicz-Bak (2009), Eichengreen and Leungnareumitchai (2004), Jiang et al (2001) respectively.…”
Section: Literature Reviewsmentioning
confidence: 99%
“…size (most frequent measure as defined by the academic studies: GDP per capita)Mu et al (2013),Bae (2012) Eichengreen et al (2008),Braun and Briones (2006),Burger and Warnock (2005),Eichengreen and Leungnareumitchai (2004) 2. qualitative assessment of the legal and regulatory framework (most frequent measures as defined by the academic studies: influence of rule of law, creditor rights, property rights, lack of capital control)Astrauskaite(2016),Laeven (2014),Stewart (2009),Adelegan and Radzewicz-Bak (2009),Burger and Warnock (2005),Eichengreen and Leungnareumitchai (2004),Fabella and Madhur (2003) 3. lending to SME segment, foreign ownership of the banksAstrauskaite (2016),Behr et al (2015),Hasan et al (2014),Hakenes et al (2014),Popov and Udell (2012),Bae (2012),Stewart (2009), Adelegan and Radzewicz-Bak (2009),Eichengreen and Leungnareumitchai (2004),Jiang et al (2001) 4. size of the sovereign bond market (most frequent measures as defined by the academic studies: sovereign debt to GDP, turnover of sovereign debt on the exchange)…”
mentioning
confidence: 99%